PERLINDUNGAN TERHADAP PELAKU TINDAK PIDANA PADA TINGKAT PENYIDIKAN DIKAITKAN DENGAN PASAL 54 KUHAP MENGENAI BANTUAN HUKUM - Indra Ariska, Dudung (Yustitia, 2015)
The suspect or defendant who has entered into the courts and in every examination is subjected to inspection, it is not as an object of inspection. Akusator principle emphasized that the object of the examination was a mistake (a criminal offense), allegedly committed by the suspect or the accused. So that the principle of presumption of innocence (Presumption of innocent) adopted in the Criminal Procedure Code should really be a guide law enforcement officials to use the principle of akusator in every examination. Criminal suspects who later in the investigation process under pressure, threats or physical violence in the part of investigators to the suspects confessed that actually did not do it. Obviously it is the deprivation of rights of the accused are actually treated badly as legal subjects